Program to evaluate crop yield loss to biotic stressors and management decision rules in variable environments - Garrett, Karen A. (My University, 2013)
This R program evaluates simulations of yield loss to biotic stressors. The rate of yield loss is determined by an autoregressive process with flexible parameters, so that different levels of mean rate, variation in rate, and autocorrelation in rate can be evaluated. The second part of the program evaluates the success rate of decisions for management based on observations of yield loss in past seasons or in the middle of the current season. The program produces three figures summarizing model results by default, and includes options that can produce additional types of summaries.
Citation: Garrett, K. A., A. Dobson, J. Kroschel, B. Natarajan,. . .Valdivia, C. (2012). Program to evaluate crop yield loss to biotic stressors and management decision rules in variable environments. Agricultural and Forest Meteorology, 170, 216-227. https://doi.org/10.1016/j.agrformet.2012.04.018